Playing Mathematics in Early Childhood Based on Semiotics - Suryaningrum, Christine Wulandari; Misyana, Misyana; Jatmikowati, Tri Endang (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
Playing mathematics in early childhood based on semiotics gives children the opportunity to identify objects, look for signs and interpret signs so that they can solve problems in games. This study aims to describe semiotic based early childhood mathematics play activities. The research was conducted at the PAUD Lab School, Muhammadiyah University of Jember. The research subjects were 5 children from group B. The results showed that the activities of playing mathematics in early childhood based on semiotics were (1) collecting information related to semiotic-based math games, (2) looking for objects that matched the game and counting the number of objects found, (3) looking for relevant signs and signs. that are relevant to the number of objects found, (4) associated with signs of knowledge that have been previously possessed and look for all signs according to the objects found, (5) the child retells the play that has been done